2003
DOI: 10.1359/jbmr.2003.18.6.1051
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Early Changes in Bone Resorption to the Reduction in Fracture Risk With Risedronate

Abstract: Changes in the level of biochemical markers of bone resorption with risedronate treatment for osteoporosis were examined as a surrogate for the decrease in fracture risk. Greater decreases in bone resorption markers were associated with greater decreases in vertebral (and nonvertebral) fractures.Antifracture efficacy of antiresorptive therapies is only partially explained by increases in bone mineral density. Early decreases in bone resorption may also play a role. We tested this hypothesis by measuring two bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
314
0
14

Year Published

2005
2005
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 549 publications
(338 citation statements)
references
References 25 publications
10
314
0
14
Order By: Relevance
“…Alendronate [10,17,18,19,20,21] Formation: BALP, PINP, PICP, OC Fracture, BMD Resorption: sCTX, uNTX, DPD Risedronate [12,22] Resorption: uDPD, uCTX, uNTX, Fracture, BMD Teriparatide [13,14,15,33] Formation: BALP, PICP, PINP Fracture, BMD Resorption: uDPD, uNTX, sCTX Raloxifene [30,31,32] Formation: BALP, PINP, OC Fracture Resorption: uCTX Early changes in BTM to monitor anti-osteoporosis therapy Similar to most chronic diseases, monitoring the efficacy of treatment of osteoporosis is a challenge. In contrast to BMD, which typically changes in response to therapy less than 2-5% per year, or a maximum of 3% in 3-6 months, most of osteoporosis therapies act by reducing or increasing individual BTM levels or their ratios by 30-200% within 3-6 months.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Alendronate [10,17,18,19,20,21] Formation: BALP, PINP, PICP, OC Fracture, BMD Resorption: sCTX, uNTX, DPD Risedronate [12,22] Resorption: uDPD, uCTX, uNTX, Fracture, BMD Teriparatide [13,14,15,33] Formation: BALP, PICP, PINP Fracture, BMD Resorption: uDPD, uNTX, sCTX Raloxifene [30,31,32] Formation: BALP, PINP, OC Fracture Resorption: uCTX Early changes in BTM to monitor anti-osteoporosis therapy Similar to most chronic diseases, monitoring the efficacy of treatment of osteoporosis is a challenge. In contrast to BMD, which typically changes in response to therapy less than 2-5% per year, or a maximum of 3% in 3-6 months, most of osteoporosis therapies act by reducing or increasing individual BTM levels or their ratios by 30-200% within 3-6 months.…”
Section: Treatmentmentioning
confidence: 99%
“…The relationships between vertebral fracture risk and changes from baseline in sCTX and uNTX were not linear (p b 0.05). In the original publication [22] below a decrease of 55-60% for sCTX and 35-40% for uNTX, the authors concluded that the decrease in bone resorption in patients taking risedronate accounts for a large proportion of the reduction in fracture risk but that there was little further improvement in anti-fracture efficacy below a decrease of 55-60% for sCTX and 35-40% for uNTX. [22].…”
Section: Treatmentmentioning
confidence: 99%
“…However, recent findings from a large fracture trial indicate no further anti-fracture benefit with further decreases in bone resorption markers below a decrease of 55% to 60% for uCTx and 35% to 40% for uNTx. 69 Further research is needed to establish the cut-offs of each bone turnover markers based on the probability of fracture in large clinical trials of each therapeutic regimen.…”
Section: Bone Turnover Markersmentioning
confidence: 99%
“…(4) The decrease in BTMs has been associated with an improvement in fracture risk resulting from anticatabolic treatment; thus larger decreases in BTMs are associated with greater fracture efficacy. (7)(8)(9)(10) The International Osteoporosis Foundation recommends that bone turnover be used for monitoring the treatment of individual patients with osteoporosis. (11) It is therefore important that we have a complete description of the change in BTMs, especially when the drug belongs to a new class and results in a distinct BTM profile compared with existing therapies.…”
mentioning
confidence: 99%